Health sector reform at the COVID cross-roads: Public goods or health markets - An agenda for health systems research - Sundararaman Thiagarajan (Wolters Kluwer Medknow Publications, 2021)
The debate around approaches to health sector reform is one of the foundational questions around which the discipline of health policy and systems research has grown. In the immediate postwar period, health and health care were recognized as areas of market failure, requiring state action in the provision of free or subsidized services. In the eighties and nineties, due to both geopolitical and ideological reasons, this understanding changed, leading to a wave of market-based health sector reforms. An academic discourse built around neoliberal economics initiated, shaped, and legitimized these reforms. Faced with worsening health outcomes and costs of care after a decade of such reforms, there was a partial reversal of policy toward improving health sector performance that relied on nonmarket solutions built around notions of solidarity, trust, and rights. In India, this took the form of the National Rural Health Mission. Examples of health systems research that supported this direction of change are discussed. In the last decade, a second wave of health sector reforms sought to make markets work by repositioning government as purchaser of health care from private providers through insurance and contracts. There is little evidence that this worked. The need to rely on public services to cope with the COVID-19 pandemic, further questioned this direction of reform. We emphasize the need to expand and develop a framework of health systems and policy studies that are more appropriate to the achievement of universal health care, health equity, and health rights in the Indian context.